2010
DOI: 10.1097/sap.0b013e3181c47d71
|View full text |Cite
|
Sign up to set email alerts
|

Grading of Severity of the Condition in Burn Patients by Serum Protein and Albumin/Globulin Studies

Abstract: Capillary permeability increases after inflammation with consequent leak of fluid, electrolytes, and proteins. The albumin molecule size being smaller (69 kDa) than the globulin molecule (90-156 kDa) will leak relatively at an early stage of the disease (with moderate increase in capillary pore size) than globulin leading to albumin/globulin reversal. In cases with severe permeability changes with rapid progression to larger pore size with simultaneous leak of both albumin and globulin, albumin/globulin revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Further, prospective studies have shown a relationship between total protein and mortality in transplant patients [ 11 ], total protein with low albumin and mortality in hospitalized patients [ 12 ], albumin-to-globulin ratio and mortality in cancer patients [ 13 15 ], IgA levels and cancer-related mortality in elderly patients [ 16 ], and hypergammaglobulinemia and decreased survival in patients with rheumatologic conditions [ 17 , 18 ]. A study of patients admitted to a burn unit with serial measures of serum albumin and protein, showed that developing a lower albumin-to-globulin ratio, which would be equivalent to a greater gamma gap, was associated with higher mortality [ 19 ]. Moreover, a recent actuarial manuscript, using billing data described serum globulins as an important predictor of mortality [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, prospective studies have shown a relationship between total protein and mortality in transplant patients [ 11 ], total protein with low albumin and mortality in hospitalized patients [ 12 ], albumin-to-globulin ratio and mortality in cancer patients [ 13 15 ], IgA levels and cancer-related mortality in elderly patients [ 16 ], and hypergammaglobulinemia and decreased survival in patients with rheumatologic conditions [ 17 , 18 ]. A study of patients admitted to a burn unit with serial measures of serum albumin and protein, showed that developing a lower albumin-to-globulin ratio, which would be equivalent to a greater gamma gap, was associated with higher mortality [ 19 ]. Moreover, a recent actuarial manuscript, using billing data described serum globulins as an important predictor of mortality [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This process peaks during the first 12–24 hours, coupled with a reduction in the albumin mRNA response to the burn and an increased synthesis and accumulation of acute-phase reactants. After this initial phase, hypoalbuminemia persists because of the lack of its synthesis, its loss through damaged skin areas, and deficiencies in nutritional support (3335). In our patients, hypoalbuminemia was closely related to the burned BSA, which is considered to have predictive value for mortality.…”
Section: Discussionmentioning
confidence: 99%
“…30 Flora et al observations comment on age as the next most important predictor in LOS once adjusted for TBSA. 22,31 Studies performed by Johnson et al 2 notes on the linear correlation in LOS in accord with TBSA within each age group. However, the linearity in correlation becomes discontinuous on increasing decile age.…”
Section: Discussionmentioning
confidence: 98%
“…Length of hospitalization for burn patients involves a complex interplay of factors such as size and depth of the burn, patient age, infection complications, patient's sex, and management protocol by the treating institution. 2,13,17,[22][23][24] A combination of the aforementioned factors provides an estimated risk of mortality and length of hospitalization; however, length of hospitalization for individual patients is still quite unpredictable. First described by Baux in 1961, the parameter of age and percentage burned established the rule of thumb for predicting mortality rate.…”
Section: Discussionmentioning
confidence: 99%